"Physicochemical, immunomodulatory and safety aspects of milks fermented with Lactobacillus paracasei isolated from kefir". (September 2019) - Bengoa, Ana A.; Iraporda, Carolina; Acurcio, Leonardo B.; de Cicco Sandes, Sávio H.; Costa, Karen; Moreira Guimarães, Gabriele; Esteves Arantes, Rosa M.; Neumann, Elisabeth; Cantini Nunes, Álvaro; Nicoli, Jaques R.; Garrote, Graciela L.; Abraham, Analía G.
Abstract: The use of Lactobacillus paracasei strains isolated from kefir grains as starters for the development of functional dairy products was evaluated. The physicochemical and immunomodulatory properties of milks fermented with L. paracasei CIDCA8339, CIDCA83123 and CIDCA83124 were analyzed. The three strains produced bioactive metabolites during fermentation, since the fermented milk supernatants were able to downregulate >75% of the induced innate immune response in vitro . Although all strains presented absence of hemolytic activity and susceptibility to antibiotics, L. paracasei CIDCA8339 presented more attractive probiotic and technological properties. Mice consuming the fermented milk with L. paracasei CIDCA 8339 did not present significant modifications in sIgA levels or TNF-α, TGF-β and IL-10 mRNA expression in ileum. Additionally, a decrease of INF-γ level in ileum and no microbiological translocation to liver and spleen was observed. These results demonstrate that L. paracasei CIDCA8339 represents a safe promising potential probiotic strain for the development of functional foods. Graphical abstract: Unlabelled Image Highlights: L. paracasei strains grow in milk producing organic acids and exopolysaccharide. Fermented milk supernatants downregulate the immune response in intestinal cells. L. paracasei strains did not show hemolysis or antibiotic resistance. Consumption of CIDCA 8339 fermented milk did not exert inflammatory response. Milk fermented with L paracasei CIDCA 8339 is innocuous to mice.